Inisiasi Kalus Bangle (Zingiber purpureum Roscoe) pada Beberapa Kombinasi 2.4-D dan Kinetin - Tarigan, Swary Dwi Suherna; Astarini, Ida Ayu; Astiti, Ni Putu Adriani (Jurnal Hortikultura Indonesia, 2023)
Bangle (Zingiber purpureum Roscoe) is belonging to the Zingiberaceae family that has been utilized as a medicinal plant. The objective of the research was to evaluate the effects of 2.4-D and kinetin on bangle’s callus initiation. This research was conducted at the Plant Tissue Culture Laboratory, Biology Study Program, Faculty of Mathematics and Natural Science, Udayana University from February until May 2023. This experiment was arranged using a Completely Randomized Design (CRD) with two factors and repeated five times. The first factor was 2.4-D’s concentration (0, 1 and 2 ppm) and the second factor was kinetin’s concentration (0, 0.5 and 1 ppm). Variables observed were callus initiation time, percentage of callus formation, and callus morphology. The result shows that 1 ppm 2.4-D - 0.5 ppm kinetin produce the fastest callus initiation time (10.8 days) and the highest callus formation percentage (100%), whereas 1 ppm 2.4-D - 0.5 ppm kinetin and 2 ppm 2.4-D - 0.5 ppm kinetin produce embriogenic callus morphology (white color and friable texture). Keywords: auxin, cytokinin, medicinal plant, Zingiberaceae